Meta Analisis Model Pembelajaran Problem Based Learning terhadap Hasil Belajar Kognitif Di Sekolah Dasar - Yusuf Darmawan; Gamaliel Septian Airlanda (Jurnal Bidang Pendidikan Dasar, 2021)
The learning model is a design that is used as a class design. Learning outcomes are changes in behavior obtained after carrying out activities in the learning process of the PBL learning model, learning can develop critical thinking skills for students. In the effectiveness of the PBL learning model, there has not been a comprehensive study of the effectiveness of learning model. The goal is to understand how much influence cognitive learning outcomes and Problem Based Learning learning models have on the learning outcomes of elementary school students. The results of the effect size test using the T-test are seen from the Paired Sample Test listed in the mean column of 49.27 and the standard deviation of 26.09 has a sig value of 0.000. The effect size obtained is 0.37 and seen from cohen's table that PBL learning has a moderate effect on cognitive learning outcomes in elementary schools.